Shell games : a novel - Kistler, Bonnie (Harper, 2024)
"A glamorous, madcap mystery following a wealthy woman of a certain age whose life is turned upside down by love - and true confessions. Kate Sawyer is a somebody, not only in Florida, but up and down the East Coast. A hugely glamorous and successful real estate developer, she has more money than she will ever need. At the age of seventy, Kate finally gets back together with her childhood sweetheart, and they get married in a gigantic wedding that is the talk of the town. Everybody, especially her thirty-something daughter, is thrilled, even though it's always been just the two of them. On their wedding night, the new husband turns to Kate and makes a stunning confession about a well-known crime from years ago, that he says he has committed. But did he? Or is Kate losing it? Or maybe he's just trying to gaslight her, so that he can take control of her assets. There's a prenup, of course, but there are always loopholes... Shell Games is a delicious psychologically thrilling dramedy of errors that will make you wonder if these people are paranoid, crazy, or just as confused as the rest of us"--